"APS pregnancy – The offspring". (October 2020) - Bitsadze, Viktoria; Nalli, Cecilia; Khizroeva, Jamilya; Lini, Daniele; Andreoli, Laura; Lojacono, Andrea; Fazzi, Elisa; Shoenfeld, Yehuda; Tincani, Angela; Makatsariya, Alexander
Background: Antiphospholipid antibody syndrome (APS) is an autoimmune disease that affects women in childbearing age. In recent years, great improvements were achieved in the management of pregnancies in these women. Prematurity could be an issue in these pregnancies, mainly due to the direct pathogenic effect of antiphospholipid antibodies (aPL) on the placental surface. Maternal IgG aPL can cross the placenta and theoretically interact with the growing fetus; it could reach the fetal brain because of the incompleteness of the fetal blood-brain barrier: whether this can have an effect on brain development is still debated. Neonatal thrombosis episodes have been described in children positive for aPL, not always associated with maternal antibody positivity, suggesting the hypothesis of a possible aPL de novo synthesis in fetus and neonates. Methods: A keyword-based literature search was conducted. We also described a case of neonatal catastrophic antiphospholipid syndrome (CAPS). Results: Offspring of patients with APS are generally healthy but the occurrence of neonatal thrombosis or minor neurological disorders were reported. Conclusions: The limited number of the available data on this sensitive issue supports the need for further studies. Clinical follow-up of children of mothers with APS seems to be important to exclude, in the neonatal period, the occurrence of aPL associated pathological events such as thrombosis, and in the long-term, impairment in learning skills or behavioral problems.